Successful salvage therapy with Daptomycin for osteomyelitis caused by methicillin-resistant Staphylococcus aureus in a renal transplant recipient with Fabry-Anderson disease - Polilli, Ennio (BioMed Central, 2012)
Daptomycin is licensed in adults for the management of Staphylococcus aureus methicillin-resistant infections, including bone and skin complicated infections. We describe for the first time its use in a renal transplant recipient for Fabry-Anderson Disease with right heel osteomyelitis. The patient was unresponsive to first-line Teicoplanin and second-line Tigecycline, whereas he was successfully treated with third-line Daptomycin monotherapy at 4 mg/Kg/qd for 4 weeks. Local debridement was performed in advance of each line of treatment.